Meniscal Allograft Interposition Combined with Proximal Row Carpectomy - Steiner, Murphy M.; Willsey, Matthew R.; Werner, Frederick W.; Harley, Brian J.; Klein, Shay; Setter, Kevin J. (Journal of Wrist Surgery, 2017)
Background Proximal row carpectomy (PRC) is contraindicated in wrists with preexisting arthritis of the proximal capitate or radiolunate fossa. Patients with these conditions frequently pursue wrist arthrodesis with its associated functional limitations.Questions/Purposes The purpose of this study was to evaluate the results of using lateral meniscal allograft interposition (LMAI), in combination with PRC, in patients with symptomatic wrist arthritis. The primary question is whether this allograft will allow wrist function comparable to that in patients having only a PRC. A secondary question was to determine the short-term longevity of the allograft.Patients/Method Between 2006 and 2012, nine wrists underwent PRC with LMAI. Patient demographics and rates of complication or graft failure were determined. During independent clinical exams, functional outcomes were reviewed, patients completed a Disabilities of the Arm, Shoulder, and Hand (DASH) scores, and radiographs were taken.Results Four patients met the inclusion criteria, having clinical follow-up at an average of 4.2 years. DASH scores at the time of follow-up ranged from 9 to 33, with an average of 24. Average radiocapitate joint space in the first postoperative radiograph was 2.8 mm compared with 1.8 mm at the time of final follow-up. No wrists went on to arthrodesis.Conclusion Early outcomes of PRC with LMAI are comparable to those results found in the literature of PRC alone. LMAI with PRC may be a valid short-term option as a motion-preserving procedure in those patients contraindicated to having a PRC alone.Level of Evidence Level IV
Keywords: proximal row carpectomy; meniscal allograft